Extraterrestrial Intelligence: Academic and Societal Implications, edited by J. Andresen and O. Chon Torres - Drake, Jeremy (Journal of Scientific Exploration, 2023)
The impact on human society of new scientific discoveries is generally a quite gradual one, and more evolutionary than revolutionary. At least on the timescales that describe our everyday lives. New physics or chemistry or biotechnology takes industry some time to assimilate, and new products often years to deploy. Today’s top discoveries in astronomy have very little impact at all, perhaps piquing the interest of society’s scientific bent for one or two news cycles, perhaps leading to revisions in a few paragraphs of the next editions of standard textbooks. New behavior observed from a black hole in a galaxy far, far away might be absolutely fascinating, but beyond those who find it so the rest of human society will continue along its merry way oblivious. Could this be about to change? Thanks to NASA’s Kepler and Transiting Exoplanet Survey Satellite (TESS) planet-finding missions, together with a slew of ground-based facilities, “exoplanets” - planets that orbit around stars other than the Sun - are now mainstream. At the time of writing, there were 5197 confirmed planets detected around other stars , a number that is steadily1 increasing as the exoplanet surveys continue providing copious new data for astronomers to sift through and look for telltale planetary signatures.